Life beyond the Paper Graphic Index: Evaluating New Geographic Retrieval Technologies for the Future Map Library - Fleet, Chris (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
In recent years technology has dramatically expanded the possibilities for making available historical maps on the web. These various new techniques are examined and evaluated. It is argued that map curators are well placed to exploit these new techniques, and doing so has a range of advantages for the future survival of our institutions. The priorities and principles that should guide this work are suggested, along with the main practical conclusions for website presentation.